2014
DOI: 10.1530/eje-14-0396
|View full text |Cite
|
Sign up to set email alerts
|

MANAGEMENT OF ENDOCRINE DISEASE: Clinical management of paragangliomas

Abstract: Paragangliomas (PGLs) are rare vascular, neuroendocrine tumors of paraganglia, which are associated with either sympathetic tissue in adrenal (pheochromocytomas (PCCs)) and extraadrenal (sympathetic paraganglioma (sPGLs)) locations or parasympathetic tissue of the head and neck paragangliomas (HNPGLs). As HNPGLs are usually benign and most tumors grow slowly, a wait-and-scan policy is often advised. However, their location in the close proximity to cranial nerves and vasculature may result in considerable morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 127 publications
0
22
0
1
Order By: Relevance
“…Symptoms of catecholamine excess are a characteristic manifestation of sPGLs, although approximately 10% to 15% of sPGLs are asymptomatic. [ 3 ] In this case, the patient suffered from hyperglycemia and was diagnosed as having diabetes for 6 years before surgery, and levels of blood glucose were gradually turned into normal after the operation, which suggested that hyperglycemia is induced by catecholamine release. In the reported 11 HPGL cases, 2 showed headache, 1 showed both headache and palpitation, and 1 female patient showed abnormal menstruation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Symptoms of catecholamine excess are a characteristic manifestation of sPGLs, although approximately 10% to 15% of sPGLs are asymptomatic. [ 3 ] In this case, the patient suffered from hyperglycemia and was diagnosed as having diabetes for 6 years before surgery, and levels of blood glucose were gradually turned into normal after the operation, which suggested that hyperglycemia is induced by catecholamine release. In the reported 11 HPGL cases, 2 showed headache, 1 showed both headache and palpitation, and 1 female patient showed abnormal menstruation.…”
Section: Discussionmentioning
confidence: 96%
“…[ 2 ] According to the World Health Organization (WHO), tumors which are related to sympathetic tissues in the adrenal gland should be named as pheochromocytomas (PCCs), whereas tumors related to extraadrenal sympathetic tissues should be named as sympathetic paragangliomas (sPGLs). [ 3 ] sPGL often occurs along the axis of the body, from skull-base to the pelvic floor and corresponds to the distribution of the sympathetic nerve. [ 4 ] In summary, PGLs include sPGLs and HNPGLs.…”
Section: Introductionmentioning
confidence: 99%
“…In basic research, the secretory behavior of the adrenal glands is usually examined through the determination of CA (and/or their metabolites) levels in the systemic blood circulation or in the urines. In clinical medicine, measurements of plasma and urinary CA and/or their metabolite levels can be used to for the diagnosis and the follow-up of several neuroendocrine tumors, such as neuroblastoma ( 8 ), paragangliomas ( 9 ), pheochromocytomas ( 10 12 ), early arterial hypertension ( 13 , 14 ), and also for evaluating hemodynamic and sympathoadrenal functions in patients in intensive cares ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, approximately 12% are considered malignant [ 1 3 ]. Accordingly, the only widely accepted criterion is the presence of metastases in organs where normally there are no chromaffin cells, as is the case of lymph nodes [ 3 , 4 ]. Extra-adrenal paragangliomas are usually diagnosed in the retroperitoneum, head, and neck.…”
Section: Introductionmentioning
confidence: 99%
“…Those located in the abdomen and pelvis are associated with the sympathetic nervous system, with catecholamine hypersecretions being the cause of the signs and symptoms during the clinical presentation, as well as the possible effects of mass on neighbouring organs [ 5 , 6 ]. The treatment of choice for this type of neoplasm is surgical resection and eventually, tumour embolisation prior to surgery or the administration of combined chemotherapy [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%